Purely cutaneous Langerhans cell histiocytosis presenting as an ulcer on the chin in an elderly man successfully treated with thalidomide - Radhakrishnan Subramaniyan; Rajagopal Ramachandran; Gnanasekaran Rajangam; Navya Donaparthi (Wolters Kluwer Medknow Publications, 2015)
Langerhans cell histiocytosis (LCH) is a rare, clonal proliferative disorder of Langerhans' cells of unknown etiology. Although the clinical presentation and therapeutic approach to the disease in children have been well established; limited data is available about the disease in adults. Purely cutaneous involvement of LCH in a man older than 70 years has rarely been described. Herein we report the case of a 71-year-old man with cutaneous LCH confined to the perioral region, scalp, and flexures successfully treated with thalidomide.